2012
DOI: 10.3109/10641963.2012.681080
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren Reduces Morning Blood Pressure in Hypertensive Patients with Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a leading disease that requires renal replacement therapy. The progression of renal dysfunction in DN is faster than the other renal diseases. While antihypertensive therapy reduces albuminuria, a good indicator for the progression, hypertension in DN is treatment resistant. Among patients with DN who took angiotensin receptor blockers (ARBs), 27 patients who exhibited poor control of albuminuria were enrolled into the study. Angiotensin receptor blocker was exchanged to aliskiren … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Strategies to downregulate the RAS include the knockdown or knockout of ANG II receptors, the use of ANG II receptor blockers that interfere with ANG II signaling, and the use of angiotensin-converting enzyme and renin inhibitors, which reduce ANG II levels by inhibiting its formation. Pharmacological tools are also effective in the treatment of hypertensive patients (70,667,702). Furthermore, ANG II-induced hypertension models can be divided into renin-dependent and low-renin models.…”
Section: Angiotensin Ii-induced Hypertensionmentioning
confidence: 99%
“…Strategies to downregulate the RAS include the knockdown or knockout of ANG II receptors, the use of ANG II receptor blockers that interfere with ANG II signaling, and the use of angiotensin-converting enzyme and renin inhibitors, which reduce ANG II levels by inhibiting its formation. Pharmacological tools are also effective in the treatment of hypertensive patients (70,667,702). Furthermore, ANG II-induced hypertension models can be divided into renin-dependent and low-renin models.…”
Section: Angiotensin Ii-induced Hypertensionmentioning
confidence: 99%
“…Interestingly, the mechanism of renal protection of aliskiren in the DN state is not achieved by lowering blood pressure. After 6 months of follow-up, aliskiren was found to reduce albuminuria levels in DN patients, but did not change the glomerular filtration rate or blood pressure ( 94 ). Studies have shown that the inhibition of ER stress may be one of its molecular mechanisms.…”
Section: Er Stress Inhibitormentioning
confidence: 99%
“…The efficacy of aliskiren on blood pressure reduction has been evaluated in animal experiments [6,7], as well as in patients with CKD [8] and diabetes [9]. The antihypertensive effect of aliskiren remains relatively long, even after treatment withdrawal [7], and is comparable or superior with that of other antihypertensive agents at recommended doses [10].…”
mentioning
confidence: 99%